The Project Manager’s Challenges During Covid-19 Pandemic - Othman, Mohd Hilmi; Ishak, Nur Aini (Journal of Advanced Mechanical Engineering Applications, 2021)
Covid-19 has affected our daily routines, particularly how we work, which is increasingly conducted virtually to avoid face-to-face interaction. The objective of this study is to provide insight on the challenges confronting project managers during the Covid-19 pandemic. This study is based on a review of the relevant literature and discusses the Covid-19 background, its influence, the Work from Home strategy, factors affecting the performance of virtual projects, and the construction sector’s issues. The article then explores and outlines the obstacles confronting project managers during the Covid-19 pandemic. In conclusion, during Covid-19, project managers’ responsibilities are increasing substantially. Due to the difficulty of the role of a project management from the start, project managers must be intellectually, emotionally, and physically prepared, especially throughout the pandemic phase, which has no end date. Additionally, they must immediately acquire new skills and information and prepare for the worst-case scenario, as this pandemic is unprecedented for anyone, and thus no one has the best guidelines to follow. Finally, project managers must be more creative in managing projects and entertaining all stakeholders to ensure that the projects continue to run smoothly and within the constraints.